Corrosive Environment Assessment and Corrosion-Induced Rockbolt Failure Analysis in a Costal Underground Mine. (4th March 2019) - Guo, Qifeng; Pan, Jiliang; Wang, Min; Cai, Meifeng; Xi, Xun
Abstract : As an effective ground-reinforcing system, rockbolts have been widely used in underground excavations. Corrosion of rockbolts has been one of the most reasons for rockbolts system failure. In this paper, the chemical composition and pH values of the groundwater in Sanshandao Gold mine are first tested. Corrosion of the slotted rockbolts used in roadways of the mine is analysed. The corrosion rate of rockbolts is evaluated based on experimental results from similar corrosive conditions. A time-dependent analytical model on anchoring force degradation caused by corrosion of the rockbolt is developed. Furthermore, the effects of corrosion rate and geometric parameters of the slotted rockbolts on anchoring force degradation are discussed. Suggestions on rockbolts support design in corrosive conditions are given. It has been found that, with the corrosion time increasing, the anchoring force between the rock and the rockbolt gradually decreases. The larger the corrosion rate is, the faster the anchoring force decreases. For long-term service roadways under corrosive conditions, a slotted rockbolt with a smaller radius and thicker wall can enhance the anchoring force.